Social Defeat, Psychotic Symptoms, and Crime in Young Caribbean Immigrants to Rotterdam - Vinkers, David J.; Van de Vorst, Micha; Hoek, Hans W.; Van Os, Jim (Frontiers in Psychiatry, 2021)
SUMMARY Background The negative experience of being excluded from the majority group (social defeat) may be associated with psychosis in immigrants. The social defeat hypothesis is supported by the high frequency of perceived discrimination and acculturation problems in psychotic immigrants. In addition, social defeat may lead to crime through social problems such as unemployment, school dropout, a broken family structure or psychotic symptoms. Methods We assessed the association between social defeat and acculturation on the one hand and broadly defined psychotic symptoms and crime on the other in Caribbean immigrants to Rotterdam aged 18 to 24 years. The municipality of Rotterdam provided data about Caribbean immigrants to Rotterdam. Acculturation, social defeat (perceived discrimination, sense of control and evaluation of self and others), psychotic symptoms and crime were assessed using online questionnaires. Results. Social defeat was associated with psychotic symptoms in women (β = .614, p < .001). This relation applied particularly to the negative self-perception domain of social defeat. Acculturation was associated with neither social defeat nor psychotic symptoms or crime and did not mediate the association between social defeat and psychosis. Conclusion The social defeat hypothesis of psychosis may be gender-specific valid but does not extend to crime.